PREPARASI FENILBUTAZON DALAM PEMBAWA VESIKULAR ETOSOM DENGAN BERBAGAI VARIASI KONSENTRASI FOSFATIDILKOLIN DAN ETANOL - Nur Illiyyin Akib; Suryani Suryani; Halimahtussaddiyah R Halimahtussaddiyah R; Niken Prawesti (Halu Oleo University, 2014)
Phenylbutazone is non steroidal anti-inflammatory drug (NSAID) used in treatment of joint inflammation such as rheumathoid arthritis. In order to minimize irritation effect on gastrointestinal tract, the dose of phenylbutazone is reduced or administered through transdermal pathways. Flux penetration of drugs across the membrane can be improved by using vesicular type of delivery system such as ethosome. This study aim to prepare phenylbutazone in ethosome vesicular system. Ethosome vesicular systems were prepared with various concentrations of phosphatidylcholine (2% and 3%) and ethanol (30%, 35%, and 40%). Vesicles that are formed further characterized by shape, size and entrapment efficiency. The shaped of ethosome produced is large unilamellar vesicle. The size of vesicle varies between 0.57 to 0.81 µm with the smallest size on Formula C. The highest entrapment efficiencies was also on the Formula C by 59.88% with 2% concentration of phosphatidylcholine and 40% of ethanol. Keywords: phenylbutazone, vesicle, ethosomes.